Reduction, Prevention, and Control of Salmonella enterica Viable but Non-culturable Cells in Flour Food - Li, Yanmei; Huang, Tengyi; Bai, Caiying; Fu, Jie; Chen, Ling; Liang, Yi; Wang, Kan; Liu, Jun; Gong, Xiangjun; Liu, Junyan (Frontiers in Microbiology, 2020)
The processing and storage conditions of flour food inevitably pose environmental stress, which promote bacteria to enter a viable but non-culturable (VBNC) state. The existence of VBNC cells causes false-negative detection in traditional culture-based detection methods, resulting in food quality and safety issues. This study aimed at investigating the influence factors including nutrition, acid, salt, and temperature for the entry into a VBNC state of Salmonella enterica and an efficient detection method. During induction with multi-stress conditions, nutrition starvation antagonizes with low-level acidity. Besides, high-level acidity was considered as an inhibitor for VBNC induction. Four inducers including nutrition starvation, salt stress, low-level acidity, and low temperature were concluded for a VBNC state. In addition, the keynote conditions for S. enterica entering a VBNC state included (i) nutrient-rich acidic environment, (ii) oligotrophic low-acidity environment, and (iii) oligotrophic refrigerated environment. Based on the keynote conditions, the environmental conditions of high acidity (1.0% v/v acetate) with low temperature (−20°C) could successfully eliminate the formation of S. enterica VBNC cells in flour food. In addition, combining with propidium monoazide pretreatment, PCR technology was applied to detect S. enterica VBNC cells. The sensitivity of the PMA–PCR technology was 105 CFU/ml in an artificially simulated food system. The results derived from this study might aid in the detection and control of VBNC state S. enterica in flour food products.